Cholinesterase Research - Korabecny, Jan; Soukup, Ondrej (Biomolecules, 2021)
Cholinesterases are fundamental players in the peripheral and central nervous systems [...].
Keywords: Neurons; Acetylcholinesterase; neuroprotektivní látky; Butyrylcholinesterase; nervový přenos; cholinesterasové inhibitory; acetylcholinesterasa; synapse; Neuroprotective Agents; Peripheral Nervous System; periferní nervový systém; butyrylcholinesterasa; Cholinesterase Inhibitors; Central Nervous System; GPI-Linked Proteins; GPI-vázané proteiny; centrální nervový systém; Gene Expression; zvířata; Humans; Synaptic Transmission; neurony; Synapses; exprese genu; neurodegenerativní nemoci; Neurodegenerative Diseases; lidé; Animals